2022
DOI: 10.1111/jfb.15234
|View full text |Cite
|
Sign up to set email alerts
|

Influence of photoperiod variations on the mRNA expression pattern of melatonin bio‐synthesizing enzyme genes in the pineal organ and retina: A study in relation to the serum melatonin profile in the tropical carp Catla catla

Abstract: Surface-dwelling C. catla were exposed to different photoperiods (8L:16D, 12L:12D, 12D:12L and 16L:8D) and the mRNA level profile of enzymes involved in melatonin synthesis was evaluated in the pineal gland and retina. Furthermore, a comparative analysis of the serum melatonin profile with the mRNA level was also performed. The results indicated diurnal variations in the transcripts of tph1, aanat and hiomt in the pineal organ and retina, and these variations change with the change in lighting regime. The seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…It was also pointed out that the rhythm parameters of various melatonin biosynthesizing enzyme genes in these two organs vary and/or shift differently. Additionally, under the influence of different photoperiodic conditions, the pattern of mRNA expression of the melatonin biosynthesizing enzyme genes in the retina and pineal organ changes 36 . This investigation reveals a distinctive way of mRNA transcripts for the genes TPH1, AANAT1, AANAT2, and ASMT in the retinal and pineal organ; the pineal melatonin biosynthesizing enzyme genes exhibited a pattern similar to that of serum levels of melatonin, and the retinal genes underwent a dramatic change with photoperiod.…”
Section: Pineal and Extra-pineal Sources Of Melatoninmentioning
confidence: 99%
“…It was also pointed out that the rhythm parameters of various melatonin biosynthesizing enzyme genes in these two organs vary and/or shift differently. Additionally, under the influence of different photoperiodic conditions, the pattern of mRNA expression of the melatonin biosynthesizing enzyme genes in the retina and pineal organ changes 36 . This investigation reveals a distinctive way of mRNA transcripts for the genes TPH1, AANAT1, AANAT2, and ASMT in the retinal and pineal organ; the pineal melatonin biosynthesizing enzyme genes exhibited a pattern similar to that of serum levels of melatonin, and the retinal genes underwent a dramatic change with photoperiod.…”
Section: Pineal and Extra-pineal Sources Of Melatoninmentioning
confidence: 99%
“…Esculenta [ 5 ] and plasma corticosterone in Bufo americanus [ 6 ]. The circadian rhythm changes in response to environmental factors, such as light [ 7 ] and temperature [ 8 ]. In our previous studies [ 9 , 10 ], we revealed the circadian rhythm of Dybowski’s frog ( Rana dybowskii ) and the impact of photoperiod on its Melatonin.…”
Section: Introductionmentioning
confidence: 99%
“…Authors demonstrate that there are diurnal variation in the expression of these genes not only occurs in the pineal gland, but also occurs in the retina (Devi et al ., 2022). The expression of the melatonin production genes in the pineal gland were concordant with serum level melatonin, however, retinal mRNA levels changed dramatically with photoperiod, confirming that the pineal gland as the main melatonin producer.…”
mentioning
confidence: 99%
“…However, in this issue a few more of those unknowns are answered by the work of Devi et al . (2022) who investigate the expression of three genes involved in the four stage enzymatic process of melatonin production ( tph1 , aanat and hiomt) in Indian carp ( Catla Catla ).…”
mentioning
confidence: 99%
See 1 more Smart Citation